Chemical Compatibility of Depacon(®) with Medications Frequently Administered by Intravenous Y-Site Delivery in Patients with Epilepsy or Head Trauma - Rashed, Sahar M. (Pediatric Pharmacy Advocacy Group, 2004)
OBJECTIVES: Intravenous Y-site administration of more than one medication through the same in-line catheter is a common practice used in the management of acute seizures. The objective of this study was to determine the compatibility of valproate sodium (Depacon(®); 2 or 20 mg/mL) with 13 medications that are frequently administered to manage seizures or are given to patients with an acute head injury who are at risk for developing post-traumatic epilepsy. METHODS: The study medications included atracurium, dexamethasone, diazepam, fosphenytoin, lorazepam, magnesium sulfate, mannitol, methyl-prednisolone, midazolam, pentobarbital, phenytoin, ranitidine, and thiopental. Equal volumes of valproate and each of the study drugs were admixed and immediately examined using several physiochemical criteria: Tyndall effect, color and pH change, gas evolution, and particle formation (HIAC/Royco liquid particle counter). Samples were also evaluated using HPLC analysis (C(18) column; methanol/tetrahydrofuran/ phosphate buffer; 44/1/55% v/v, at 1.5 mL/min; 50°C) with UV (190-400 nm) photodiode detection. The valproate peak (220 nm) was quantified by both peak area and height. Samples were analyzed within 5 minutes of admixture and were reassessed at 15 and 30 minutes. RESULTS: With the exception of diazepam, midazolam, and phenytoin, all of the remaining drugs were chemically compatible with valproate, both in 5% Dextrose Injection, USP(D5W) and in 0.9% Sodium Chloride Injection, USP (Normal Saline -NS). None of the compatible medications produced a significant pH change, discernible gas, particle formation, reduced valproate titer by HPLC analysis (coefficient of variability < 1.5%), or the temporal formation of unidentified UV absorbing (190–400 nm) peaks. CONCLUSIONS: Intravenous valproate is compatible with most agents employed in seizure management or used in patients at risk for seizures following head injury and is safe for concurrent Y-site drug administration.